Fashionable addiction : the impact of digital identity through the cult of the body (an African perspective, with particular reference to the Democratic Republic of Congo) - Mbikayi, Maurice (Michaelis School of Fine Art, 2015)
My MFA project consists of sculptural installations, videos and images that, together with the written text, comment on the impact of information technology on society. In both the written and practical components, I refer to my own experience and developments in fashion and access to information technology (IT) in my home country, the Democratic Republic of the Congo (DRC), with a focus on Kinshasa. I also explore aspects of the consumerist nature of IT in Africa more broadly and how this generates trends relating to ‘FOMO’, an internet slang acronym for the Fear Of Missing Out. My primary reason for connecting African fashion with contemporary computer technology is because both concern Western products being utilised in Africa in the context of self-determination. The African continent is a source of mining wealth, for example coltan (short for columbite-tantalite), a mineral widely used in technology. The DRC is one of the major coltan-producing countries, and yet it is technologically underdeveloped or limited itself because of an oppressive capitalist system (Pole Institute – blood minerals [PI], 2010: 8-9), (PI, 2010). However, some of these minerals return to Africa in the form of products and create new consumers, desires and services in emerging contemporary technology contexts. In the process of upgrading to higher levels of technology, the developed world often uses Africa as a dumping zone for electronic waste (e-waste), with no regard for the environmental and human impact. For example, the UN environment programme's 2012 and 2013 report under the Waste for Electrical and Electronic Equipment (WEEE) legislation showed that thirty percent of the allegedly second-hand products imported to Ghana were useless (African WEEE Report by the UN Environment Programme [AWRUNEP], 2012). Pieter Hugo's photographs in the book Permanent Error (2011) provide strong visual evidence of this. Although I’m aware of the debate around issues of representation and ‘afro pessimism’ generated by Hugo’s images, my motivation in using them is that they provide sufficient documentation of the realities of disposing of electronic waste and the impact on people and the environment pertaining to those particulars zones of Africa. I draw an analogy between the consumption of IT and African fashion, and specifically with my own country's culture of dressing-up, which has developed into a kind of doctrine (the ‘cult of the cloth’) and an expression of resistance. The analogy is linked to the desire to stay up to date with IT, which can lead to addiction. I also consider it useful to compare the symbolic and aesthetic aspects of African customs of hairdressing, the wearing of hats and jewellery, and even body modification as a social identification with today's society, within which ‘personal media’ are additional accessories for urban status. My reference and use of computer parts critique the way that contemporary technology has become an extension of our personal style, as in the fashion sense described above: a virtual identification which could also suggest a tendency towards an alienation of the body (because of the virtual social interaction and virtual identity) from its immediate environment that has manifested in our current psychological landscape. Consequently, I suggest the consumption of contemporary media in urban spaces opens up the notion of virtual anthropology or virtual cultural anthropology, related to the electronic personality or e-personality.